A Solar-Powered Automated Alternating Wetting and Drying System for Sustainable Paddy Field Irrigation - Zainol, Anis Najihah; Mohamad, Khairul Anuar (Journal of Electronic Voltage and Application, 2026)
This paper presents the design and implementation of a solar-powered automated irrigation system based on the alternating wetting and drying (AWD) technique for paddy field cultivation. The system is designed to enhance water-use efficiency and reduce reliance on manual irrigation by harnessing renewable solar energy. Water level sensors are employed to monitor field conditions and automatically regulate irrigation cycles in accordance with AWD principles. A solar photovoltaic (PV) system provides renewable power to the ESP32 microcontroller and sensor, enabling reliable operation in off-grid and remote areas. Prototype testing using a scaled paddy field model is conducted to evaluate the irrigation control strategy and PV system performance. The solar PV system demonstrated a voltage range of 12.5-15.6 V, with peak power output of 99.8 W under clear-sky conditions, and exhibited a strong linear relationship between irradiance and power output (R² = 1.00). The automated AWD control using an ultrasonic water-level sensor achieved reliable irrigation triggering with measurement errors below 10%, enabling accurate detection of dry and normal field conditions. These results confirm that the solar-powered AWD system provides reliable off-grid operation while maintaining effective and precise water management for paddy cultivation.